New species of Ballusia Ginsburg and Morales, 1998 (Ursidae, Carnivora) from Miocene of Eastern Siberia, Russia. (3rd April 2021) - Sotnikova, Marina; Klementiev, Alexey; Sizov, Alexander; Tesakov, Alexey
ABSTRACT: The new basal ursine bear, Ballusia zhegalloi n. sp., is described from the Early Miocene Tagay 1 locality (Baikal region, Russia) based on isolated M1. Previously described maxillary fragment with M1-2 from the closely synchronous fauna of Khirgis-Nur I in Mongolia, originally referred to Ballusia elemensis, is here included into the new species. The M1 of the new species shares similarities with M1 of previously known Early Miocene European species B. elmensis but is more derived in lower medial cusps, transversally closer spaced medial ridge and lingual cingulum, and by a slightly expressed antero-external angle. The new Asian species shares some derived features with Ballusia orientalis from Early Miocene of China, such as a more rounded M1 outline, and incipient buccal styles in M1. The other characters in the two forms of Asian Ballusia imply their parallel evolution. The Tagay find represents the first record of the genus Ballusia in Russia. It elucidates phyletic affinities of early ursine bears and refines the geographic and stratigraphic range of the genus Ballusia .